Self-Confidence Profile of Students At Panawangan 1 State Senior High School in 2025 - Sazkia Nuril Pathmi; Yandi Cahya Yundani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Self-confidence refers to an individual’s sense of trust and belief in their own abilities, which plays a crucial role in students’ academic engagement, emotional well-being, and personal development. In the educational context, self-confidence influences students’ willingness to participate in classroom activities, express opinions, take academic risks, and cope with learning challenges. This study aims to examine the level of self-confidence among twelfth-grade students at SMA Negeri 1 Panawangan. The population of the study comprised 270 students, from which 162 students were selected as research samples using a random sampling technique to ensure representativeness. The study employed a descriptive quantitative research design to provide an objective overview of students’ self-confidence levels. Data were collected through a structured questionnaire designed to measure various aspects of self-confidence, including belief in personal abilities, optimism, independence, and emotional control. The collected data were analyzed using descriptive statistical techniques to determine the distribution of self-confidence levels among students. The findings indicate that the majority of twelfth-grade students at SMA Negeri 1 Panawangan fall into the moderate category of self-confidence, accounting for 49% or 79 students. This result suggests that, although students generally possess an adequate level of self-confidence, there remains considerable room for improvement. The findings highlight the importance of supportive educational environments and targeted interventions to strengthen students’ self-confidence as a foundation for academic success and future readiness.